2020
DOI: 10.18805/ijar.b-3897
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Growth Performance and Genetic Parameters of Three Varieties of Domesticated Japanese Quail

Abstract: The quantitative genetic study involving a pure line mating of 160 pairs of three varieties of domesticated Japanese quails (CARI-Ujjawal; CARI-Suneheri and CARI-Brown) were maintained under individual pedigree cages for breeding. A total of 6221 quail chicks from three hatches comprising three varieties were used for this study. Among them, CARI-Ujjawal has higher hatchability with less rearing mortality percentage. CARI-Ujjawal had highest (plessthan0.01) body weight at all ages when compared to the other tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…On the other hand, the obtained results of our Barbary partridge during 3 years prove to be similar to those of (Mezerdi, 2011). Concerning the physiological characteristics, we demonstrated that the age of chicks and their genotype influence on the energetic needs of birds, which was confirmed by Hassan and Delpech (1986) on chickens and Monika et al, (2020) on Japanese quail. In addition, the food consumption depends on the optimal energetic level of aliment of partridges after 8 weeks of breeding (Özek, 2004) and depends on the environment in nature (Didillon, 1988) and broiler diets significantly improved their performance (Rokade et al 2018).…”
Section: Resultssupporting
confidence: 80%
“…On the other hand, the obtained results of our Barbary partridge during 3 years prove to be similar to those of (Mezerdi, 2011). Concerning the physiological characteristics, we demonstrated that the age of chicks and their genotype influence on the energetic needs of birds, which was confirmed by Hassan and Delpech (1986) on chickens and Monika et al, (2020) on Japanese quail. In addition, the food consumption depends on the optimal energetic level of aliment of partridges after 8 weeks of breeding (Özek, 2004) and depends on the environment in nature (Didillon, 1988) and broiler diets significantly improved their performance (Rokade et al 2018).…”
Section: Resultssupporting
confidence: 80%
“…Quail can be exploited for meat production due to their short incubation period (Azahar et al, 2018), short periods of growth and maturation of the youth (Monika et al, 2020;Redoy et al, 2017) and the good laying in the first eight months period (Jatoi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Various anatomic, genetic and breeding studies of this bird species used for breeding are available in reference information (Kumari et al 2008;Hertamawati et al 2019;Demiraslan et al 2014;Demircioglu et al 2019;Demircioglu et al 2020;Monika et al 2020). In this study, we analyzed digits angle and digits length ratio of Japanese quail using geometric morphometric analysis.…”
Section: Introductionmentioning
confidence: 99%